Evaluation of chemical and biological insecticides to control Frankliniella occidentalis (Thysanoptera: Thripidae) in asparagus crops - BUSTILLO-PARDEY, ALEX ENRIQUE (Revista Colombiana de Entomología, 2009)
Frankliniella occidentalis is an important pest in flower and vegetable crops. This insect presents high populations in asparagus crops for exportation in Ica, Peru. Besides the damage it causes to the crop, its importance is greater due to American and European market restrictions, which do not allow the presence of insects in the final product. On the other hand, the use of insecticides is restricted given regulations on residues that could be present in this crop. In a first experiment, eight chemical insecticides and in a second one, two strains of Beauveria bassiana, were tested in asparagus crops with heavy infestations of F. occidentalis. The insecticides were: ciromazina 75 WP, abamectina 50 EC, tiametoxam 25 WG, lambda cyhalothrina 50 EC, lufenuron 50 EC, imidacloprid 200 SC, cartap 50 WP and fipronil 200 SC, at dosages recommended by the manufacturers, plus an untreated control. Results showed that lufenuron, abamectina and fipronil caused the highest mortalities two days after application, but at five days no products showed control. This was probably due to migration of thrips populations from adjacent fields, to possible insecticide resistance, or that the tested products had no residuality. The applications of B. bassiana at a dosis of 2 x 1013 spores/ha gave acceptable control, prolonging the effect up to 16 days after application. Highest mortality (64.8%) was reached at eight days. This entomopathogen is considered promising in the population management of F. occidentalis.